Biological treatment of Hydrothermal Liquefaction (HTL) wastewater: Analytical evaluation of continuous process streams. (April 2021) - Torri, Cristian; Kiwan, Alisar; Cavallo, Martina; Pascalicchio, Paolina; Fabbri, Daniele; Vassura, Ivano; Rombolà, Alessandro Girolamo; Chiaberge, Stefano; Carbone, Rosa; Paglino, Roberto; Miglio, Roberta
Graphical abstract: Highlights: Hydrothermal liquefaction wastewater (HTWW) can be processed biologically. Most of HTWW organics are readily fermented to volatile fatty acids. Methanogenic activity is hampered by low concentration of strong inhibitors. Anaerobic-aerobic biological treatment without dilution was effective. 97 % COD reduction was obtained with 220 days residence time. Abstract: In order to deal with hydrothermal liquefaction wastewater (HTWW), a new anaerobic-aerobic continuous process was developed. The process, which included a sequence of Up-Flow Anaerobic Sludge Blanket (UASB) and downstream aerobic Continuously Stirred Tank Reactor (CSTR), was tested on the HTWW obtained from Waste to Fuel® demo plant developed by ENI s.p.a. [1 ]. Performance of the system was evaluated in term of methane yield and chemical oxygen demand (COD) abatement capability. Detailed fate of organic compounds was evaluated through different analytical techniques, highlighting main issues and potential of HTWW biological treatment. The system was fed with neat HTWW (189 gCOD L −1 ) for 2.5 y, with variable organic loading rate (OLR) and minimal external inputs. UASB reactors converted most of HTWW organics into volatile fatty acids (VFA) and methane with concurrent precipitation of oily like insoluble, whereas aerobic CSTR removed VFA from anaerobic effluent. Under regime conditions (ORL equal to 0.5 gCOD L −1 d −1 ) COD decreased from 189 to 6.6 gCOD L -1, showing 97 % COD abatement with the coupled anaerobic-aerobic treatment. Such a COD abatement was obtained by means of multiple effects, namely biomethanation, precipitation of organic matter and aerobic oxidation of fermentation products (VFA produced in anaerobic digestion) and subsequent aerobic oxidation (in downstream aerobic reactor). These effects accounted for 43, 40 and 17 % of the total COD decrease, respectively. Inhibition phenomena were the key challenge for improving methane yields and system productivities. The overall results confirmed that valorization of HTWW is a feasible task, albeit rather challenging.